Dose and spatial resolution analysis of grating-based phase-contrast mammography using an inverse Compton x-ray source - Heck, L.; Eggl, E.; Grandl, S.; Dierolf, M.; Jud, C.; Günther, B.; Achterhold, K.; Mayr, D.; Gleich, B.; Hellerhoff, K.; Pfeiffer, F.; Herzen, J. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Although the mortality rate of breast cancer has been reduced with the introduction of screening mammography, many women undergo unnecessary subsequent examinations due to inconclusive diagnoses. Therefore, spatial resolution and soft tissue contrast must meet very high standards. The former is necessary in order to be able to detect and distinguish closely spaced microcalcifications from each other. Thus, a high spatial resolution is demanded. Superposition of anatomical structures especially within dense breasts in conjunction with the inherently low soft tissue contrast of absorption images compromises image quality. This can be overcome by phase-contrast imaging. In this study, we analyze the spatial resolution of grating-based multimodal mammography dose-dependently using a mammographic phantom and one freshly dissected mastectomy specimen at an inverse Compton X-ray source. Here, the main focus was on estimating the spatial resolution with the sample in the beam path and discussing benefits and drawbacks of the method used as well as the estimation of the mean glandular dose. Finally, the possibility of improving the spatial resolution is investigated by comparison of the monochromatic grating-based mammography with the standard one. In almost all cases, the spatial resolution is higher in our proposed approach while the dose can be significantly reduced. Additionally, phase-contrast imaging helps to improve the detection of tumor lesions.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Inverse Compton X-rays; Mammography; Phase-contrast imaging; Radiation; Spatial resolution